2020
DOI: 10.1038/s41598-020-75035-3
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Tip60 HAT mediated neural histone acetylation homeostasis is an early common event in neurodegenerative diseases

Abstract: Epigenetic dysregulation is a common mechanism shared by molecularly and clinically heterogenous neurodegenerative diseases (NDs). Histone acetylation homeostasis, maintained by the antagonistic activity of histone acetyltransferases (HATs) and histone deacetylases (HDACs), is necessary for appropriate gene expression and neuronal function. Disruption of neural acetylation homeostasis has been implicated in multiple types of NDs including Alzheimer’s disease (AD), yet mechanisms underlying alterations remain u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 80 publications
1
18
0
Order By: Relevance
“…Further, these Tip60/HDAC2 binding alterations at specific gene loci are present before Aβ accumulation is detectable, supporting these sites as potentially valuable early AD biomarker 'hot spots' that are easy to track. Recently, we reported that disruption of Tip60 and HDAC2 balance in the brain is a common event in other neurodegenerative diseases modelled in D. melanogaster: Huntington's disease, amyotrophic lateral sclerosis, and Parkinson's disease [44]. Further studies may reveal a therapeutic potential for targeting Tip60 in these disorders as well.…”
Section: Discussionmentioning
confidence: 98%
“…Further, these Tip60/HDAC2 binding alterations at specific gene loci are present before Aβ accumulation is detectable, supporting these sites as potentially valuable early AD biomarker 'hot spots' that are easy to track. Recently, we reported that disruption of Tip60 and HDAC2 balance in the brain is a common event in other neurodegenerative diseases modelled in D. melanogaster: Huntington's disease, amyotrophic lateral sclerosis, and Parkinson's disease [44]. Further studies may reveal a therapeutic potential for targeting Tip60 in these disorders as well.…”
Section: Discussionmentioning
confidence: 98%
“…Kat5 is a major histone acetyltransferase that plays important roles in the regulation of DNA repair, autophagy, proteasome-dependent protein turnover, and learning and memory. Disruption of Kat5 mediated histone acetylation was an early common event in neurodegenerative disorders including AD ( Beaver et al, 2020 ; Li and Rasmussen, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most retained introns were degraded by the NMD pathway due to the premature termination codons in the newly formed transcript. However, some mRNAs may bypass NMD and be translated ( Beaver et al, 2020 ; Li and Rasmussen, 2020 ). Li HD et al performed integrative functional genomic analysis of RI in AD and observed remarkable correlations of RI transcripts within innate immune genes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, these Tip60/HDAC2 binding alterations, at specific gene loci, before Aβ accumulation is detectable, support these sites as potentially valuable early AD biomarker “hot spots” that are easy to track. Recently, we reported that disruption of Tip60 and HDAC2 balance in the brain is a common event in other neurodegenerative diseases modeled in Drosophila : HD, ALS, and PD (Beaver et al, 2020). Further studies may reveal a therapeutic potential for targeting Tip60 in these disorders as well.…”
Section: Discussionmentioning
confidence: 99%